Differential correlates of autobiographical memory specificity to affective and self-discrepant cues - Wessel, I; Postma, I; Huntjens, R; Crane, C; Smets, J; Zeeman, G; Barnhofer, T (Psychology Press Ltd, 2014)
According to the CaRFAX model (Williams et al., 2007), several processes may result in overgeneral autobiographical memory. The present study examined whether the type of cue used in the Autobiographical Memory Test (AMT) is important for illuminating relationships between autobiographical memory specificity and variables pertinent to the Functional Avoidance (FA) and Capture and Rumination (CaR) aspects of the model. Sixty-one women varying in their experience of a potentially traumatic event and previous depression completed two versions of the AMT: one containing affective cues and the other containing cues representing idiosyncratic self-discrepancies. Consistent with the FA hypothesis, avoidance of the potentially traumatic event was associated with fewer specific memories on the affective, but not the self-discrepant AMT. Furthermore, in line with the CaR hypothesis, performance on the self-discrepant, but not the affective AMT was related to ruminative self-reflection in women reporting previous depression, even after controlling for current depression and education levels. Together the results suggest that varying cue type may increase the sensitivity of the AMT, depending on the aspect of the CaRFAX model of overgeneral memory that is to be addressed. © 2013 Taylor and Francis.